The development of an e-workload distribution system: a focus on the fair distribution of teaching workloads of lecturers / Asma Hanee Ariffin ... [et al.] - Ariffin, Asma Hanee; Abdul Wahid, Rohaizah; Sulaiman, Suliana; Mansor, Marzita; Abd Wahab, Mohd Helmy (Universiti Teknologi MARA, 2020)
Studies have shown excessive teaching workloads of teachers and lecturers have become a contentious issue in the academic realm, making them physically and emotionally strained. Therefore, this study was carried out to develop a workload distribution management system called e-WLOAD to help the management of universities in distributing workloads that are fair and acceptable to all lecturers. In this study, the researchers used the Evolutionary Prototyping method for the development of e-WLOAD. A series of interviews involving a head of a department, a faculty dean and an academic registrar as well as the analysis of the Academic Workload Guidance Document of the Malaysian Qualifications Agency (MQA) and the academic Annual Performance Assessment Report were carried out to reveal the relevant criteria for the distribution of lecturers’ workloads, namely Status, Minimum and maximum credits, Lecturer classification, Current Teaching Status, and Teaching Load Requirements. After running the system, the results of the functionality test indicated that the prototype had fulfilled all system requirements successfully based on such distribution criteria.